The deictics aquí, acá, ahí, allí and allá in "Tell them not to kill me!" by Juan Rulfo - Gavilán Sierra, Yan Carlos (2022)
Rulfo's aesthetics explicitly presents us with the presence of demonstratives on the textual surface aquí, acá, ahí, allí and allá conjugated in the narrative, either manifested by the narrator or through the voice of the characters who adopt the rural perspective. Thus, in this article, we study the deictic system aquí, acá, ahí, allí and allá in the short story «Tell them not to kill me!» by Juan Rulfo from the perspective of the traditional system of deictics and the cognitive perspective raised by Stradioto and Maldonado (2018), with the aim of making explicit the dynamics and variabilities that these deictic systems acquire in the indicated story. For this purpose, the documentary method (Galeano, 2004) is used, which allows coding and systematizing precisely, and text tinguistics for the analysis of the deictics present in the textual surface of the mentioned story. Finally, it is concluded that the deictics present in the story «Tell them not to kill me!» present variability of meaning, a fact that corroborates the approach of Stradioto and Maldonado.